Learners Pronunciation Ability and Communicative Drilling Technique at eleventh Grade of SMKN 4 Sidrap - Ismail Ma'sa; Sam hermansyah (La Ogi : English Language Journal, 2022)
The objective of the research were to find out : (1) whether or not the ability the use of Communicative Drilling increased pronunciation ability of the second year students at SMK 4 Sidrap and (2) whether or not the second year students of SMK 4 Sidrap are interested in pronunciation through Communicative Drilling. This research applied Pre-experimental method that apllied one group pretest and posttest. The subject of the research was the second year students of SMK 4 Sidrap academic year 2021.total number of population was 92 students spread in three classes and one class of them XI.3 were taken as sample by using cluster sampling technique. The data of the research were collected by using twi kinds of instruments, namely pronunciation test and questionnaire. Pronunciation test was used to obtain data of the students’ pronunciation ability and questionnaire was used to know the students interest in pronunciation by using communicative drilling. The result of data analysis showed that the mean score of post test (70) was higher than the mean score of post test ( 28). This showed that was significant difference between the students before and after taught by using communicative drilling. Then, the analysis of interest by using Linkert Scale indicated that the students were interested to pronounce English through communicative drilling. It was proved by mean score of students’ interest was (79.9) in categories in interest.The result of the t-test value (7.29) was greater than t-table (α = 0,05: 16 = 2.120). This mean that H1 was accepted. Based on data analysis, the researcher concluded that teaching pronunciation by using Communicative Drilling increased the students’ ability to pronounce English. Moreover, the use of Communicative drilling makes the students’ interested in pronouncing English.